The Analisis Hubungan antara Dimensi Big Five Personality dengan Riwayat Kecelakaan Truk antar Provinsi - Anggraini, Novita Lizza; Malik, Anis Rohmana; Anwar, Putri Gesan Prabawa; Fadana, Irfan Andri; Jingga, Dinar Padang Mutiara; Ramadhani, Tyas Ayu (SPECTA Journal of Technology, 2025)
Based on data from the National Transportation Safety Committee, traffic accidents involving trucks in East Kalimantan resulted in four fatalities, one serious injury, and 29 minor injuries. This study aims to determine the relationship between working hours, rest periods, and personality dimensions through the Big Five Personality theory with the accident history of inter-provincial truck drivers. The study uses an analytical design with a cross-sectional approach. The research subjects are truck drivers selected using purposive sampling techniques, with a sample size of 30 for the Big Five Personality measurements and 15 truck units for vibration measurements. This is a quantitative study. The results show that there is no significant relationship between respondent characteristics, such as age, education, work duration, and length of service, and the history of work accidents. Vibration measurements indicate that 12 out of 15 truck units operated by drivers have vibration levels above the threshold limit value (TLV), which is 0.8660 during an 8-hour exposure period.